Behavior of concrete subjected to compression loads including the SRD as an absorsion energy device, using recycled tire sheets - Tovar Rodríguez, Jorge Frank (2024)
In this research the lineal and nonlinear behavior of concrete was studied with the purpose of increasing the energy abortion capacity in order in can be used in common buildings for low resources communities and held in highly seismic zones. Recycled tires from Disused Tires were used to elaborate the SRD (Steel-Rubber Device) which consist of rubber layers of 5mm thickness and steel layers of 2mm thickness, with circular shape of 5cm diameter and put one on another like a “sandwich”. This device was placed inside the concrete samples. The specimens were of four types: conventional (PC, without SRD) and modified (PM, with SRD), the last ones were of three sub-types according to the number of rubber layers between steel layers (PM1, PM2 and PM3). Experimental compression tests were taken according to the standard ASTM C469 and complemented with numerical test on finite element analysis on a reliable software. Results showed that the SRD reduce the compression strength in 13% to 17% range and decrease the modulus of elasticity as well in 3.30% to 10% range, both in relation to the conventional samples. On the other hand, the SRD increased the energy dissipation capacity through a gradually damage developing and higher residual strains in the modified samples.